Research on metrics models for cloud services information security evaluation - Yue-ming LU; Zhi-hui ZHANG (网络与信息安全学报)
Due to the lack of metric standards and the metric imprecise problems of cloud service information secu-rity,the research status of the relevant standards at home and abroad were introduced.As for the demand for infor-mation security measurement requirements of the trusted cloud,the advantages and disadvantages of metric models based on the trusted root were analyzed.At last,the future research direction which was to study a scalable com-bined,real-time,privacy protected,easy to transplant and less cost metrics model was pointed out.